The effects of thymoquinone and cytozine arabinoside on apoptosis and cell proliferation in acute myeloide leukemia - Aslı Altun; Nurten Kara; Şengül Tural; Alişan Yıldıran; Leman Tomak (Global Journal of Cancer Therapy - Peertechz Publications, 2022)
Purpose: The aim of this study was to investigate the effects of a chemotherapeutic agent Cytosine Arabinoside (Ara-C) and a natural anticancer agent of Thymoquinone (TQ) on apoptosis and cell proliferation of AML cell lines (Kasumi-6) both alone and in combined form. Material and method: Kasumi-6 AML cells were treated with three different doses of Ara-C (0.1, 0.5 and 1 µmol) and TQ (25, 50 and 100 µM) for 48 and 72 hours incubations. After Annexin V and Propidium Iodide (PI) staining, apoptosis, viability, and cell proliferation were evaluated for each group in flow cytometry. Results: As a result, AML cell lines showed a statistically significant difference in a single treatment of the active substances. Their combined treatment showed an increase in apoptosis and a decrease in viability in both groups at 48 and 72 hours incubation times (p < 0.001). In each group, it was observed that apoptosis was increased and viability was decreased and consequently cell proliferation was suppressed. Conclusion: Ara-C was used for the first time in this study with TQ in AML. It was determined that the combined use of TQ and Ara-C did not have a synergistic effect on apoptosis.